Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

Analysis of blood-based DNA methylation signatures of aging and disease progression in inflammatory bowel disease - Trevor Doherty; Edel McDermott; Sarah Jane Delany; Hugh Mulcahy; Therese M. Murphy (Human Genetics, 2025)
Inflammatory bowel diseases (IBDs) are chronic inflammatory disorders influenced by environmental factors and characterised by a dysregulated immune response. DNA methylation (DNAm) a key epigenetic mechanism plays a role in the etiology of complex diseases like IBD. Epigenetic clocks which estimate biological aging through DNAm patterns have also been linked to various health states, including IBD. Previously, we profiled DNA methylation in peripheral blood from adult IBD patients and controls using the Illumina 450K microarray ( n = 184). We now expand this dataset with 8-year clinical follow-up data, including disease progression and treatment response. Additionally, we generate second and third-generation epigenetic clock measures in this cohort to investigate if IBD patients exhibit epigenetic age acceleration compared to healthy controls. We identified one CpG site (cg03583111) significantly differentially methylated in IBD patients with long-term clinical recurrence (after the first year of study) compared to non-recurrence (no treatment escalation after 8 years). We assessed DNAm aging signatures in IBD patients versus controls, finding evidence of significant epigenetic age acceleration, as measured by three epigenetic clocks (GrimAge, GrimAge2, and DunedinPACE), in IBD patients compared to controls. These associations were replicated in two independent IBD cohorts: adult (GSE87648, n = 377) and paediatric (GSE112611, n = 238). Moreover, we observed higher age acceleration (GrimAge, U = 669, p = 0.003) and a faster pace of aging (DunedinPACE, t = 3.233, p = 0.002) in patients with active UC compared to inactive disease, but not for CD. These findings suggest that blood-based DNAm signatures could serve as biomarkers for detecting, monitoring, and classifying IBD.

Dual X-ray absorptiometry detects disease- and treatment-related alterations of bone density in prostate cancer patients - Gillian L. Smith; Alan P. Doherty; Linda M. Banks; Jane Dutton; Iain W. Hanham; Timothy J. Christmas; Richard J. Epstein (Clinical & Experimental Metastasis, 2000)